Species composition and diversity along the elevational gradient of a low tropical hill in Teramuo Hill, Bau, Sarawak, Malaysia - Tonga, Noweg; Jongkar, Grinang; Julia, Nelson; Bridgette, Philip; Selvana Eyra, Felix; Meekiong, Kalu (Society for Indonesian Biodiversity, 2024)
Numerous efforts have been made to study the diversity pattern of trees in Nature Reserves in the Bau District of Sarawak, Malaysia. However, studies on tree diversity along the elevational gradient in the district's low tropical hills still need to be completed. This study sought to evaluate the composition and diversity of tree species on a low tropical rainforest hill in the Bau District of Sarawak. The study's specific objectives include: (i). Identifying the species composition at different elevations and (ii). Measuring the species diversity and richness across different elevational gradients. The study site was Teramuo Hill, a 9.2-hectare local recreational area in Bau District, Sarawak, belonging to a Bidayuh village community. The hill encompasses three forest types (primary, secondary, and agroforest) and has suffered degradation from both human activity and natural causes. A total of 28 sampling sites were arranged in six vertical lines along the elevational gradient, with the lowest elevation being below 45 meters above sea level (m asl.) and the highest about 100 m asl.. The study found that the species composition and species types dominating at different elevations varied. A distinct pattern emerged in species diversity and richness across the elevational gradient. Between 61 and 75 m asl., the mid-elevation zones exhibited the highest species diversity. These results suggest that the main influences are ecological factors and habitat physical variability at different elevations. The findings are essential for understanding how minor elevation changes affect tree communities in tropical forest environments. This knowledge can assist in planning targeted conservation programs and dictate community priorities in the Bau District of Sarawak, Malaysia.